The outcome of carpal tunnel syndrome with modified mini-incision technique. - Kalhoro, Aurangzeb; Abdul Sattar M Hashmi; Sattar, Abdul Basit (International Journal of Endorsing Health Science Research, 2021)
Background: Median nerve compression in hand at the level of transverse ligament leads to numbness and pain in the hands, which results in discomfort in daily routine work has a psychological impact. The objective of the present study was to evaluate the modified mini-incision at the transverse crease in carpal tunnel syndrome. Methodology: A prospective descriptive study was conducted at Neurospinal & cancer care Institute, Karachi, from January 2012 – February 2020. Patients who were diagnosed with clinical symptoms, positive Phalen and Tinel test and confirmed with EMG finding of carpal tunnel syndrome were included in the study. Patients were operated through modified mini-incision at the transverse crease. The outcome was recorded in the form of pain relief, healing time with restoration of daily life activity and scar adhesion on follow-up. Results: A total of 97 patients were included. The male to female ratio was 1:7.8. The mean age was 40 ± 19.5 years. The right hand was 72.2%, the left hand was 13.4%, and the bilateral was 14.4%. VAS score improved 2 grades in 96%, and pinch grip improved in 98% of patients in one month. Only 2% of patients had stiffness after surgery Conclusion: Minimal incision carpal tunnel release has shown positive outcome in median nerve compression, having limited skin incision, safe, feasible and minimizing the scar assist help in early return to work.